1995
DOI: 10.1002/1097-0142(19951201)76:11<2319::aid-cncr2820761121>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin for the correction of cancer associated anemia with and without concomitant cytotoxic chemotherapy

Abstract: Background. Chronic anemia is a common complication in patients with cancer, especially in those with advanced disease or who are under intensive chemotherapy. Because homologous blood transfusions involve some hazards, the safety and efficacy of recombinant human erythropoietin (r‐HuEPO) in the treatment of anemic patients with cancer with and without concomitant chemotherapy were studied. Methods. One‐hundred two cancer patients with hemoglobin less than 11 g/dl, ferritin greater than 30 μg/l, and creatinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
2
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 36 publications
10
43
2
5
Order By: Relevance
“…Numerous studies, both placebo-controlled and open-label, have consistently shown that increasing haemoglobin values has a measurable and significant effect on QOL parameters in cancer patients whether they are receiving (Abels, 1993;Case et al, 1993;Henry and Abels, 1994;Leitgeb et al, 1994;Glaspy et al, 1997;Demetri et al, 1998) or not receiving concurrent chemotherapy (Ludwig et al, 1995). In all of these studies, haemoglobin was increased by the administration of recombinant human erythropoietin (rHuEPO, epoetin alfa).…”
Section: Improved Quality Of Lifementioning
confidence: 99%
“…Numerous studies, both placebo-controlled and open-label, have consistently shown that increasing haemoglobin values has a measurable and significant effect on QOL parameters in cancer patients whether they are receiving (Abels, 1993;Case et al, 1993;Henry and Abels, 1994;Leitgeb et al, 1994;Glaspy et al, 1997;Demetri et al, 1998) or not receiving concurrent chemotherapy (Ludwig et al, 1995). In all of these studies, haemoglobin was increased by the administration of recombinant human erythropoietin (rHuEPO, epoetin alfa).…”
Section: Improved Quality Of Lifementioning
confidence: 99%
“…Moreover, many chemotherapy patients suffer from a chronic state of exhaustion, known as fatigue syndrome. This syndrome occurs frequently in combined radiation, endocrine, and chemotherapy regimens (25). It leads to reduced quality of life and may be associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
“…It is produced in response to tissue hypoxia, mainly (85-90%) by renal tubular interstitial cells [6] and to a minor degree also by liver and bone marrow (BM) macrophages [7], Red cell transfusion carries the risk of transmission of infections as well as transfusion reactions. Administration of EPO has convincingly been shown to increase haematocrit and decrease transfusion requirement in 40-70% of patients with chronic anaemia of cancer [8,9]. It also prevents or ameliorates anaemia in patients undergoing chemotherapy with or without cisplatin [8,10] and improves haemoglobin levels in HIV infected patients experiencing anaemia while receiving zidovudine treatment [11].…”
Section: Clinical Application Of Erythropoietin In Chronic Anaemia Ofmentioning
confidence: 99%